THE SCOPE OF CIRCULAR ECONOMY IN THE HEALTHCARE SECTOR IN THE INDIAN CONTEXT - Kalra, Aayushi; Khurana, Anil; Bali, Shivani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The use of the circular economy in India’s healthcare sector is encouraged by environmental concerns and aims to keep the economy sustainable(S. et al., 2017) Additionally, since India is home to the largest population in the world and is expanding rapidly, its healthcare sector is creating a lot of waste and using up many resources.(Voudrias, 2018)Notably, following the circular economy model can help address these challenges, by making the most of resources and reducing environmental impact(Salvioni & Almici, 2020). Recently, it has been observed that Indian healthcare facilities are choosing circular economy ideas to replace the old linear systems by using resources more economically and having a smaller impact on the environment(Guzzo et al., 2020). The event of the pandemic has made us understand that our traditional healthcare systems need to be improved and that stronger and sustainable approaches need to be implemented to maintain excellent care and protect the environment (Baudier et al., 2022).